Pharmacognostic study of Vernonia ferruginea, Vernonia polyanthes and Vernonia westiniana species - Camargo, Ely Eduardo Saranz (Seven Editora, 2024)
Introduction: Medicinal plants have always been a reason for discussion, the knowledge of their use dates back to past times in the history of civilization. Vernonias are species known as "assa-peixe", and Vernonia polianthes, popularly, is widely used for the treatment of various pathologies. This study aims to carry out pharmacognostic methods to identify species of Vernonia ferrugínea, Vernonia polyanthes and Vernonia westiniana  The identification of a species becomes difficult when the plants are acquired in the form of powders, dry extract or in liquid form such as tinctures and extracts. In this way, pharmacognostic tests were carried out, facilitating the identification of the species. Methodology: Based on physical and chemical methods, described in the Brazilian Pharmacopoeia VI edition and on the website of the Brazilian Society of Pharmacognosy, some tests were carried out to identify secondary metabolites present in the species: Vernonia ferrugínea, Vernonia polyanthes and Vernonia westiniana. Results and Discussion: In the results obtained, chemical reactions and physical methods were found, which provided safe identification of the species studied. In the determination of the ash content, it is possible to differentiate them, being more evident through chemical methods, than through reactions, the presence of flavonoid glycosides, alkaloids, terpenes and saponnic compounds was determined. Another practical method that provided an identification of the compound 3,7dimethyl-quercetin, isolated by high performance liquid chromatography (HPLC), was the comparative thin layer chromatography (CCCD), which verified the presence in Vernonia polyanthes and was not found in Vernonia westiniana. From the same isolated substance it was possible to quantify it in methanol extracts and in the infusion, and higher concentrations were found in extracts of Vernonia ferruginea and lower concentrations in infusion of Vernonia polyanthes. Conclusion: From this pharmacognostic study, it was possible to establish a method of identification of Vernonias species, however, for better safety it is necessary to use more technologically modern methods.  DOI:https://doi.org/10.56238/sevened2024.018-073